Key Competencies of a Teacher of Russian Language and Literature as the Basis for Effective Teaching (Eurasian Journal of Philology Science and Education, 2026)
The article is devoted to the study of professional competencies of teachers of Russian language and literature in modern educational standards. The study shows the relevance of the topic in terms of the challenges of the 21st century, including the rapid development of technology, rethinking teaching methods and the mandatory professional training of teachers who are able to combine traditional and innovative methods. The purpose of the study is to analyze the structure, content and significance of the teacher's key competencies, such as subject, methodological, communicative, information-digital and personal. The article analyzes their impact on the quality of education and upbringing of students, including the prospects for their formation and development in educational activities. Primary attention is paid to the multifunctional nature of pedagogical competencies, which include both professional knowledge and skills, as well as personal qualities. The article describes examples of the use of these competencies, including the adaptation of material for students with different degrees of education, the use of digital tools, providing opportunities for direct communication, as well as motivating students through an individual approach. The results of the study show that the professional competencies of a teacher of Russian language and literature are the most important means of successful pedagogical activity. The presented recommendations, table, and lesson examples can be used to design training and advanced training programs for teachers, as well as to integrate innovative techniques.Keywords: competence, Russian language and literature, key competencies, progressive learning, innovative methods.